2018
DOI: 10.1111/pedi.12693
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index standard deviation score and obesity in children with type 1 diabetes in the Nordic countries. HbA1c and other predictors of increasing BMISDS

Abstract: Obesity rate in children with T1D in the Nordic countries is high, however, with country differences. Low HbA , long diabetes duration, higher insulin dose, pump treatment and experiencing a SH predicted higher BMISDS. Diabetes caregivers should balance the risk of obesity and the benefit of a very low HbA

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
24
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 39 publications
(83 reference statements)
12
24
3
Order By: Relevance
“…In our study, we found that that girls with T1D had higher BMI Z‐score compared with both boys with T1D and healthy peers. This observation was in concordance with several other studies including a very large study, investigating BMI Z‐score in 11.500 children and adolescents with T1D from Denmark, Iceland, Norway, and Sweden . In our study, BMI Z‐score correlated negatively to CTX Z‐score (and not OCN Z‐score) which could explain why CTX Z‐score was significantly lower in girls compared with boys, as girls had significantly higher BMI Z‐scores compared with the boys with T1D.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, we found that that girls with T1D had higher BMI Z‐score compared with both boys with T1D and healthy peers. This observation was in concordance with several other studies including a very large study, investigating BMI Z‐score in 11.500 children and adolescents with T1D from Denmark, Iceland, Norway, and Sweden . In our study, BMI Z‐score correlated negatively to CTX Z‐score (and not OCN Z‐score) which could explain why CTX Z‐score was significantly lower in girls compared with boys, as girls had significantly higher BMI Z‐scores compared with the boys with T1D.…”
Section: Discussionsupporting
confidence: 93%
“…Enhanced metabolic control to lower HbA 1c often improves hyperlipidaemia which benefits cardiovascular health 8 . However, optimizing treatment in order to lower HbA 1c levels has been suspected to be related to increased BMI and obesity, 9,10 with a possible negative effect on cardiovascular health 11,12 . In general, the effects of increased childhood BMI on cardiovascular outcomes later in life might, to some extent, be mediated through adult BMI 13 .…”
Section: Introductionmentioning
confidence: 99%
“…As known anabolic effects of insulin, and by using intensive insulin regimen, excessive weight gain and obesity are another common problem in children with T1DM. Increased BMI in youth with T1DM has been reported in clinic-based and national cohorts and is associated with a more atherogenic cardiovascular disease risk profile [33,34]. In a retrospective study from Australia 20-year follow-up of 1975 children with type 1 diabetes, the proportion of overweight and obese children was higher than that in the general Australian pediatric population [35].…”
Section: Discussionmentioning
confidence: 94%